“I was a 555-pound freak”: The Self, Freakery, and Sexuality in Celesta ‘Dolly Dimples’ Geyer’s Diet or Die - Nicholas, Jane (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2010)
This paper analyses former sideshow performer Celesta Geyer’s autobiography Diet or Die (1968). Despite her unusual employment in a freak show, Geyer’s autobiography fits the standard popular narrative of the disciplining of the fat body in order to achieve an idealized thin body. On the surface, the text reads as an absolute rejection of fat identity — a word that Geyer often associates with freakery. Yet, Geyer’s autobiography also shows how she became a subject through enfreakment, and it subtly reveals deep ambivalences regarding weight, sexuality and freakery. Part autobiography, part self-help manual, and part dieting advice manual, the text is a remarkably complex reflection of aspects of American culture and society in the early to mid twentieth century that has deep resonances in today’s fat phobic, dieting obsessed culture. Geyer’s autobiography also highlights the difficulties of reading and interpreting autobiographies as self-evident presentations of personal history and raises questions of how individuals tell their own stories.